Effect of post-ECAP aging on the microstructure, hardness and impact behaviour of 6061 Al alloy. (2021) - Rominiyi, A.L.; Oluwasegun, K.M.; Olawale, J.O.; Shongwe, M.B.; Adetunji, A.R.
Abstract: The effect of post-ECAP aging on the microstructure, hardness and impact behaviour of peak aged 6061 aluminium alloy after a single pass was studied in this work. SEM observations revealed the presence of the strengthening phase of Mg2 Si of varying morphology within the matrix of the as-received, T6 tempered alloy and post-ECAP aged samples. The ECAPed alloy showed a significant increase in hardness with a decline in notch toughness than the as-received alloy. Application of post-ECAP aging on the ECAPed alloy resulted in a further increase in the hardness and notch toughness of the post-ECAP aged alloy when compared with the ECAPed alloy. This can be ascribed to the precipitation of the strengthening phase which predominates the recovery of the matrix during the post-ECAP aging process. Hence, post-ECAP artificial aging resulted in an optimum combination of properties of the investigated 6061 aluminium alloy.